Development and Characterization of Human Cerebral Organoids: An Optimized Protocol. Issue 3 (March 2018) - Yakoub, Abraam M.; Sadek, Mark
Studies of human neurodevelopmental disorders and stem cell–based regenerative transplants have been hampered by the lack of a model of the developing human brain. Stem cell–derived neurons suffer major limitations, including the ability to recapitulate the 3-dimensional architecture of a brain tissue and the representation of multiple layers and cell types that contribute to the overall brain functions in vivo. Recently, cerebral organoid technology was introduced; however, such technology is still in its infancy, and its low reproducibility and limitations significantly reduce the reliability of such a model as it currently exists, especially considering the complexity of cerebral-organoid protocols. Here we have tested and compared multiple protocols and conditions for growth of organoids, and we describe an optimized methodology, and define the necessary and sufficient factors that support the development of optimal organoids. Our optimization criteria included organoids' overall growth and size, stratification and representation of the various cell types, inter-batch variability, analysis of neuronal maturation, and even the cost of the procedure. Importantly, this protocol encompasses a plethora of technical tips that allow researchers to easily reproduce it and obtain reliable organoids with the least variability, and showcases a robust array of approaches to characterize successful organoids. This optimized protocol provides a reliable system for genetic or pharmacological (drug development) screens and may enhance understanding and therapy of human neurodevelopmental disorders, including harnessing the therapeutic potential of stem cell–derived transplants.